Engaging patients in balanced scorecard evaluation - An implication at Palestinian hospitals and recommendations for policy makers - Amer, Faten; Neiroukh, Haroun; Abuzahra, Saad; AlHabil, Yazan; Afifi, Mufeeda; Shellah, Duha; Boncz, Imre; Endrei, Dóra (Frontiers in Public Health, 2022)
Introduction A balanced scorecard (BSC) is a comprehensive performance evaluation (PE) tool. A recent review summarized that a balanced consideration of PE from six perspectives in hospitals must be considered: financial, customer, internal, external, knowledge and growth, and managerial. However, patients were rarely engaged in BSC implementations. This research aims to engage Palestinian patients in BSC implementation to develop recommendations for policy makers. Methodology In this cross-sectional study, the BSC-PATIENT survey was distributed between January and October 2021. We evaluated patients’ experiences and their attitudes toward BSC dimensions (BSCP ATT). The differences in evaluations based on admission status were analyzed using Mann‒Whitney U test. Causal relationships between patients’ experiences and attitudes were analyzed using multiple linear regression. We tested the multicollinearity of the model. Path analysis was performed to understand the BSC strategic maps based on the Palestinian patients’ evaluations. Results Out of 1000 surveys, 740 were retrieved. The mean scores for Palestinian patient experiences evaluation showed that the services experience factor had the highest score (87.7 ± 17.7), and the patient care experience factor had the lowest score (57 ± 34.5). Patient experiences collectively predicted 56.4% of the variance in the BSCP ATT. The experience factors of information (β=0.400, t=13.543, P<0.001), patient care (β=0.241, t=8.061, P<0.001), services (β=0.176, t=6.497, P<0.001), and building (β=0.177, t=6.308, P<0.001) had the highest impact on BSCP ATT. The price had only a weak negative influence (β=-0.051, t=-2.040, P=0.042). Accessibility to hospitals did not have any impact on BSCP ATT. Significant differences between inpatient and outpatients’ evaluations in regard to experiences related to patient care (P=0.042), services (P<0.001), accessibility (P<0.001), and BSCP ATT (P=0.003) were found. Conclusion BSC-PATIENT successfully engaged patients in BSC PE at Palestinian hospitals. This research provides strong evidence for the impact of patients’ information experience on their attitudes. Palestinian health policy makers must prioritize the design and delivery of patient education programs into their action plans and encourage a two-way information communication with patients. Strong evidence for patient care, services, and building experiences role in improving patients’ attitudes was found. Managers should enhance patients’ feedback and engagement culture in Palestinian hospitals.